2005
DOI: 10.1007/s11199-005-7136-6
|View full text |Cite
|
Sign up to set email alerts
|

Fraternity Membership, the Display of Degrading Sexual Images of Women, and Rape Myth Acceptance

Abstract: The present study was conducted to learn more about the association between fraternity membership and attitudes and behaviors associated with sexual aggression against women. A male experimenter took digital pictures of all of the images of women displayed in the rooms of 30 fraternity men and 30 non-fraternity men on a residential, small, liberal arts college campus. The men also filled out a rape myth acceptance scale. A total of 91 images were found in the form of posters, "pin-ups," advertisements, or comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 29 publications
(29 reference statements)
5
69
0
2
Order By: Relevance
“…Based on previous research which has indicated that male groups (i.e., fraternities and sports groups) and prison settings generate an environment conducive to the intensification of misogyny (Kupers, 2010) and RMA (e.g., Bleecker & Murnen, 2005;Boeringer, 1996;Forbes et al, 2006;Koss & Gaines, 1993;Sawyer et al, 2002), it was predicted that imprisonment would have a significant positive effect on stereotypical thinking about rape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous research which has indicated that male groups (i.e., fraternities and sports groups) and prison settings generate an environment conducive to the intensification of misogyny (Kupers, 2010) and RMA (e.g., Bleecker & Murnen, 2005;Boeringer, 1996;Forbes et al, 2006;Koss & Gaines, 1993;Sawyer et al, 2002), it was predicted that imprisonment would have a significant positive effect on stereotypical thinking about rape.…”
Section: Discussionmentioning
confidence: 99%
“…Koss and Dinero (1988), for example, reported that sexually aggressive men had more associations with groups supporting dominating views of women; while, in another study, Bleecker and Murnen (2005) reported that fraternity men were more likely to endorse rape supportive attitudes than non-fraternity college men. Other research has also revealed that fraternity men hold more traditional gender role beliefs (Schaeffer & Nelson, 1993) and stronger male dominance attitudes (Kalof & Cargill, 1991) than non-fraternity men.…”
mentioning
confidence: 97%
“…Research has consistently shown that fraternity and sorority members are more likely than non-members to report traditional gender role attitudes, which promote a male-dominant, femalesubmissive model of gender (Bleecker & Murnen, 2005;Corprew & Mitchell, 2014;Kalof & Cargill, 1991;Robinson, GibsonBeverly, & Schwartz, 2004), and traditional gender role attitudes have been consistently linked to rape-supportive attitudes (Page, 2008). In a study of incoming freshmen, McMahon (2010) found that while women intending to pledge sororities were less accepting of rape myths than men intending to pledge fraternities, women intending to pledge a sorority were more accepting of rape myths than women not intending to pledge.…”
Section: Sexual Assault and Attitudes About Rape In Greek Organizationsmentioning
confidence: 99%
“…The body of scholarship that considers gender-related issues in college fraternities focuses mostly on homophobia (Case, Hesp, & Eberly, 2005;DeSantis & Coleman, 2008;Hesp & Brooks, 2009;Rhoads, 1995;Trump & Wallace, 2006), binge drinking and alcohol abuse (Borsari & Carey, 1999;Cashin, Presley, & Meilman, 1998;Caudill et al, 2006;Kuh & Arnold, 1993;Park, Sher, Wood, & Krull, 2009), hazing (Jones, 2004Kimbrough, 1997;Nuwer, 1999;Sutton, Letzring, Terrell, & Poats, 2000), and sexual violence against women (Bleecker & Murnen, 2005;Boeringer, 1996;Boswell & Spade, 1996;Koss & Gaines, 1993;Menning, 2009;Sanday, 2007). This research is disproportionately focused on predominantly white fraternity chapters at residential colleges and universities.…”
Section: Masculinities and College Fraternitiesmentioning
confidence: 99%